Comparison of two different dosages of celecoxib with diclofenac for the treatment of active ankylosing spondylitis: results of a 12-week randomised, double-blind, controlled study. Issue 3 (6th July 2007) - Sieper, J; Klopsch, T; Richter, M; Kapelle, A; Rudwaleit, M; Schwank, S; Regourd, E; May, M
Abstract : Objectives: To demonstrate the non-inferiority of celecoxib compared with diclofenac in subjects with ankylosing spondylitis (AS). Methods: The basis of the present work was a 12-week randomised, double-blind, controlled study in active AS subjects with three treatment arms: celecoxib 200 mg once a day, celecoxib 200 mg twice a day, and diclofenac SR 75 mg twice a day. The primary efficacy endpoint was the change from baseline in global pain intensity on a visual analogue scale (VAS) at week 12. Secondary endpoints covered changes in disease activity, functional and mobility capacities, and adverse events. Results: A total of 458 subjects were randomly assigned to either celecoxib 200 mg once a day (n = 153), celecoxib 200 mg twice a day (n = 150), or diclofenac (n = 155). Least square (LS) mean changes from baseline at week 12 on a pain VAS were clinically relevant in all treatment groups (celecoxib 200 mg once a day: −29.1 mm; celecoxib 200 mg twice a day:–31.7 mm; diclofenac:–32.7 mm) and non-inferior when compared to diclofenac. Ankylosing Spondylitis Assessment Study group 20% (ASAS 20) response and mean improvement in Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) scores at week 12 were numerically better on celecoxib 200 mg twice a day (59.7% and–1.32 points) and on diclofenac (60.2% and–1.48 points) than on celecoxib 200 mg once a day (46.0% and–0.99 points). The incidence of gastrointestinal adverse events was significantly higher on diclofenac (28.4%) than on celecoxib 200 mg once a day (15.0%) or 200 mg twice a day (16.7%). Conclusions: The efficacy of celecoxib 200 mg once a day and 200 mg twice a day was comparable to that of diclofenac 75 mg twice a day with respect to pain reduction. Celecoxib 200 mg twice a day and diclofenac reduced some parameters associated with inflammation more effectively than celecoxib 200 mg once a day. Treatment was well tolerated, with celecoxib (either dose) exhibiting less frequent gastrointestinal adverse events than diclofenac.